2018
DOI: 10.1111/pim.12522
|View full text |Cite
|
Sign up to set email alerts
|

Parasitized Natural Killer cells do not facilitate the spread of Toxoplasma gondii to the brain

Abstract: Summary Toxoplasma gondii is a protozoan parasite capable of invading immune cells and co‐opting their migratory pathways to disseminate through the host. Natural Killer (NK) cells can be directly invaded by the parasite and this invasion alters NK cell migration, producing a hypermotile phenotype. However, the consequences of this hypermotile phenotype for the dissemination of T. gondii to the brain remain unknown. To address this, C57BL6/J mice were infected with freshly egressed tachyzoites (type II Prugnia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…[147][148][149] It has been shown, however, that parasite-infected NK cells were defective for host defense. 150 Furthermore, it is uncertain if NK cell IFNγ is actually beneficial during infection, as it was reported that antibody-mediated NK cell depletion did not affect the survival of T. gondii-infected mice. 151 Interestingly, ILC1s represent a primary IFNγ-secreting population during acute infection with T. gondii.…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…[147][148][149] It has been shown, however, that parasite-infected NK cells were defective for host defense. 150 Furthermore, it is uncertain if NK cell IFNγ is actually beneficial during infection, as it was reported that antibody-mediated NK cell depletion did not affect the survival of T. gondii-infected mice. 151 Interestingly, ILC1s represent a primary IFNγ-secreting population during acute infection with T. gondii.…”
Section: Intracellular Pathogensmentioning
confidence: 99%
“…A small number of studies have investigated whether parasite infection of NK cells affects their behavior (4749). NK cells can be parasitized, however, this occurs at a very low frequency in vitro and in vivo .…”
Section: Ilc and Toxoplasma Gondiimentioning
confidence: 99%
“…These infected NK cells display a hypermotility phenotype and defective function. A recent study indicates that infected NK cells do not contribute to parasite dissemination in the mouse (47). Thus, how direct parasite infection of NK cells impacts the disease course is not known and needs to be further explored.…”
Section: Ilc and Toxoplasma Gondiimentioning
confidence: 99%
“…However, the consequences of this phenotype for dissemination of T. gondii into the brain remain unknown. Similarly, a mouse study found no evidence for a role for hypermotile NK cells in delivery of parasites to the brain during acute infection with T. gondii (Petit-Jentreau et al, 2018). In order to disseminate effectively within host cells many intracellular pathogens first infect leukocytes, which they use as a vehicle to transport them to target organs.…”
Section: Immune-mediated Control Of T Gondiimentioning
confidence: 99%